A training program based on HIIT improves the athletic performance of triathletes through improvements in muscle power (Revista horizonte, 2021)
Objective: This study aimed to examine the effect of a 5-week high-intensity intermittent training (HIIT)-based running plan on athletic performance and to compare the physiological and neuromuscular responses during a sprint-distance triathlon before and after the HIIT period. Methods: Thirteen triathletes were matched into 2 groups: the experimental group (EG) and the control group (CG). The CG was asked to maintain their normal training routines, whereas the EG maintained only their swimming and cycling routines and modified their running routine. Participants completed a sprint distance triathlon before (pre-test) and after (post-test) the intervention period. In both pretest and posttest, the participants performed 4 jumping tests: before the race (baseline), postswim, postcycling, and postrun. Additionally, heart rate was monitored (HRmean), whereas rate of perceived exertion (RPE) and blood lactate accumulation (BLa) were registered after the race. Results: No significant differences (p≥0.05) between groups were found before HIIT intervention (at pretest). Significant group-by-training interactions were found in vertical jumping ability and athletic performance: the EG improved jumping performance (~6–9%, p 0.7), swimming performance (p = 0.013, ES = 0.438), and running time (p = 0.001, ES = 0.667) during the competition, whereas the CG remained unchanged (p≥0.05, ES